Software Baseado em MATLAB® para Cálculo e Análise Tridimensional de Campos Elétricos e Magnéticos em Linhas de Transmissão - Freitas, Caio Augusto Fonseca de (2017)
With the publication of the report presented by Wertheimer and Leeper (1979) pointing to a possible association between childhood cancer and the electric and magnetic fields generated by power transmission lines, the concern about those fields has increased, leading to a number of studies on the subject. Although concrete evidence of this relationship was not found, rules were created establishing limits for human exposure to the fields generated by the transmission system. In order to comply with these standards, even at the designing stage, the fields are calculated and analyzed. The objective of this process is to verify whether the results meet the regulations or not. This work proposes a MATLAB® based software, which aims to facilitate this analysis. It calculates the fields generated by single and double circuit lines, and presents three-dimensional graphs as a result. The validation of the proposed software was made through case studies, in which three transmission lines of the Companhia Hidro Elétrica do São Francisco were analyzed, and the results were compared with reports about studies previously made by the company.